Loyalitas Pelanggan : Dimensi Kualitas Layanan Jasa Pada AUTO 2000 - Chandra Nugraha; Rusmin Nuryadin (Jurnal Ekonomi Manajemen Perbankan, 2019)
After-sales services are based on consumer needs, desires and requests. By paying attention to the quality of services provided to consumers, it is expected that companies can provide value, satisfaction, and quality that is in accordance with what consumers want. Thus companies can create long-term relationships with consumers or create customer loyalty.The results of the study concluded that the quality of after-sales service has an effect on customer loyalty on the Soekarno Hatta Bandung Auto 2000 with a linear regression equation Y = -3,051 + 0,735 X which means that every increase in the quality of after-sales service value will increase customer loyalty by 0,736 units. The correlation coefficient (r) = 0.952 means that there is a very strong (positive) relationship between the quality of after-sales service and customer loyalty. The coefficient of determination (Kd) = 90.7% means that the quality of after-sales service affects customer loyalty by 90.7%. The value of tcount (16,482)> t table (2,048) states that H0 is rejected and Ha is accepted, meaning that the quality of after-sales service has an effect on customer loyalty.